Pendampingan Persiapan Skenario New Normal Pada Taman Kanak-Kanak Dan Pendidikan Anak Usia Dini Di Kabupaten Kediri - Kusumawardhany, Sayekti Indah; Hariyanti, Sri (Aktualisasi Pengabdian Masyarakat, 2023)
The COVID-19 pandemic is not the first time this has occurred. Even so, the problem of covid 19 becomes serious when the transmission process is so fast, namely through contact or dopplet media. In 2020, at the beginning of the new school year, the government imposed a new normal system for school trials using the face-to-face system again with several attached rules so that the implementation of teaching and learning activities continued. This method uses socialization media. This socialization was chosen at one of the kindergartens and early childhood education in Kediri Regency, namely TK Kusuma Mulia Seketi in Kediri Regency. The socialization activity for the new normal scenario can be concluded that the Kusuma Mulia Seketi Kindergarten school can prepare some of the necessities needed for school activities that will reopen during the new school year. This socialization is expected to help schools provide adequate, safe and maximum educational services while still complying with applicable regulations.